Simulation and experimental measurement of acoustic intensity on sonication parameters and decellularization using sonication treatment - ., Nurul Syazwani; Shafiq, Mohammad; Ushida, Takashi; Noor Azmi, Azran Azhim (J-Stage, 2015)
A novel sonication decellularization system is developed to prepare complete decellularized tissue. The objective of the study is to determine the influence of acoustic intensity on sonication parameter and decellularization using sonication treatment. The distribution of acoustic intensity for sonication treatment is first demonstrated by simulation followed by experimental measurement. The relation of acoustic intensity with sonication parameter on decellularization is further investigated. The effect of acoustic intensity on decellularization is evaluated by measuring the residual cell in tissue sample using Hematoxylin-Eosin staining. The simulation shows low residual cells upon high acoustic intensity. From the result, acoustic intensity shows positive correlation with dissolved oxygen concentration and pH and negative correlation with conductivity. The present study concludes that decellularization performed by sonication treatment is dependent on acoustic intensity.